Incomplete adherence among treatment-experienced adults on antiretroviral therapy in Tanzania, Uganda and Zambia. (28th January 2015) - Denison, Julie A.; Koole, Olivier; Tsui, Sharon; Menten, Joris; Torpey, Kwasi; van Praag, Eric; Mukadi, Ya Diul; Colebunders, Robert; Auld, Andrew F.; Agolory, Simon; Kaplan, Jonathan E.; Mulenga, Modest; et al.
<x xml:space="preserve">Abstract</x> Objectives: To characterize antiretroviral therapy (ART) adherence across different programmes and examine the relationship between individual and programme characteristics and incomplete adherence among ART clients in sub-Saharan Africa. Design: A cross-sectional study. Methods: Systematically selected ART clients (≥18 years; on ART ≥6 months) attending 18 facilities in three countries (250 clients/facility) were interviewed. Client self-reports (3-day, 30-day, Case Index ≥48 consecutive hours of missed ART), healthcare provider estimates and the pharmacy medication possession ratio (MPR) were used to estimate ART adherence. Participants from two facilities per country underwent HIV RNA testing. Optimal adherence measures were selected on the basis of degree of association with concurrent HIV RNA dichotomized at less than or greater/equal to 1000 copies/ml. Multivariate regression analysis, adjusted for site-level clustering, assessed associations between incomplete adherence and individual and programme factors. Results: A total of 4489 participants were included, of whom 1498 underwent HIV RNA testing. Nonadherence ranged from 3.2% missing at least 48 consecutive hours to 40.1% having an MPR of less than 90%. The percentage with HIV RNA at least 1000 copies/ml ranged from 7.2 to 17.2% across study sites (mean = 9.9%). Having at least 48 consecutive hours of missed ART was the adherence measure most strongly related to virologic failure. Factors significantly related to incomplete adherence included visiting a traditional healer, screening positive for alcohol abuse, experiencing more HIV symptoms, having an ART regimen without nevirapine and greater levels of internalized stigma. Conclusion: Results support more in-depth investigations of the role of traditional healers, and the development of interventions to address alcohol abuse and internalized stigma among treatment-experienced adult ART patients.